Seasonal Changes in the Sorption Activity of Water-soluble Polysaccharides in Scotch Pine Cones (Pinus sylvestris L.) - D. K. Gulyaev; V. D. Belonogova (Разработка и регистрация лекарственных средств, 2022)
Introduction. Currently, there is much tension around the issue of increasing the efficiency of use of forest resources. One of these resources are scotch pine cones, which remain at the felling areas. Polysaccharides of scotch pine cones have a significant sorption activity; however, it remains unclear does the month, when raw materials were collected, affect the sorption activity.Aim. The research of the content, sorption activity and molecular weight of water-soluble polysaccharides of scotch pine cones in different seasons of the year.Materials and methods. Water-soluble polysaccharide complex (WSPC) of scotch pine cones was obtained with a method based on the well-known scheme for the carbohydrates separation according to Bailey et al. WSPC was obtained from the samples of scotch pine cones collected from July till March. Determination of the content of scots pine cones WSPC was spectrophotometrically carried out, with the modified Draywood anthrone-sulfurous method. The sorption activity of polysaccharides was determined by the methylene blue. The molecular weight of polysaccharides was identified by the viscosimetric method.Results and discussion. The content of WSPC in scotch pine cones from July till March was identified. The highest yield of WSPC was registered in winter (3.24 ± 0.31 %), and the lowest in summer (0.46 ± 0.01 %). The sorption activity of scotch pine cones WSPC in terms of methylene blue from July till March was researched in vitro. It was found that WSPC has the highest sorption activity in October (230.69 ± 4.18 %) and November (243.30 ± 9.43 %). The WSPC sorption activity is above the activity of standard medications: absorbent carbon (230.9 ± 2.34 mg/g) and colloidal silicon dioxide ("Рolisorb MP") (211.5 ± 1.87 mg/g). The average molecular weight of scotch pine cones WSPC from July till March was determined. The average molecular weight of WSPC is in the range from 6 872,27 to 21 598,06. The dependence of the scotch pine cones WSPC sorption activity on the molecular weight was registered.Conclusion. The water-soluble polysaccharide complex of scotch pine cones, obtained at different seasons, has different sorption activity, which depends on a polysaccharide molecular weight. The highest content and sorption activity of scotch pine cones WSPC matches with the period of wood production, which stipulates a practical use of cones and directions for future research.